2003
DOI: 10.1128/aac.47.12.3942-3944.2003
|View full text |Cite
|
Sign up to set email alerts
|

Singleand Double Mutations in gyrA but Not in gyrB AreAssociated with Low- and High-Level Fluoroquinolone Resistance in Helicobacterpylori

Abstract: In one French hospital the rate of resistance to ciprofloxacin in Helicobacter pylori was 3.3% (2 of 60 strains) in 1999. The six resistant clinical strains (four from 1996 and two from 1999) and three ciprofloxacin-selected single-step mutants studied carried one gyrA mutation but none in gyrB. Clinafloxacin and garenoxacin were the most active fluoroquinolones against these mutants. Occurrence of a second gyrA mutation was associated with high MICs of all fluoroquinolones tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
125
2
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(141 citation statements)
references
References 12 publications
9
125
2
4
Order By: Relevance
“…Therefore, the ideal treatment for H. pylori infection is still far from being reached and more effective and better tolerated alternative regimens are needed (16). Conversely, resistance to fluoroquinolones remains a rare occurrence, varying from 3.3% in France (17), 4.7% in the Netherlands (18), 3.9% in five Eastern European countries (19), and a high resistance rate of 20.9% in Portugal (20). And the data on the primary resistance to moxifloxicin are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the ideal treatment for H. pylori infection is still far from being reached and more effective and better tolerated alternative regimens are needed (16). Conversely, resistance to fluoroquinolones remains a rare occurrence, varying from 3.3% in France (17), 4.7% in the Netherlands (18), 3.9% in five Eastern European countries (19), and a high resistance rate of 20.9% in Portugal (20). And the data on the primary resistance to moxifloxicin are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are few reports of acquired double mutations in gyrA, Tankovic et al reported two strains with double mutations in gyrA that were highly resistant to fluoroquinolones. 15 Our study showed that STFX-containing regimens might lead to the accumulation of double mutations in gyrA with a certain degree of probability. Since both N87 and D91 are binding sites for fluoroquinolones, 8 it is reasonable that the N87 and D91 double mutation would provide stronger resistance to STFX than either mutation alone.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding mutations in other genes, previous reports showed that fluoroquinolone resistance was not associated with gyrB mutations in H. pylori. 5,9,15 The genes encoding topoisomerase IV (parC/parE) mutations are representative resistant mechanisms for fluoroquinolones in several bacteria; however, the absence of genes for topoisomerase IV (parC, parE) in H. pylori has been demonstrated. 17 Further studies are needed to clarify fluoroquinolone resistance mechanisms beyond gyrA.…”
Section: Discussionmentioning
confidence: 99%
“…Combined therapy was initially very effective, although mutations in 23S RNA [23], pbp1A [24], gyrA [25], frxA or rdxA [26], conferring resistance to each of the above mentioned antibiotic have been described, and in some populations has become so common, that the Maastricht IV consensus report urges local monitoring of H. pylori resistance [22].…”
Section: H Pylori and Antibiotic Resistancementioning
confidence: 99%